Calliphoridae fly infestation preference on meat containing borax: Supporting forensic science studies - Dewi, Mutiara Yuliana; Watiniasih, Ni Luh; Sukmaningsih, A. A. S. A. (Jurnal Biologi Udayana, 2025)
This study was conducted with the aim of determining the preference of Calliphoridae fly infestation on meat containing borax as a support for forensic science studies. The study was conducted at the Animal Taxonomy Laboratory of the Biology Study Program, Udayana University and lasted for about five months starting from January to May 2024. This study was conducted using an experimental method with 6 treatments and 4 replications. The sample in this study was pork weighing 100 grams which was given a treatment of borax glycerin with different volumes. Treatment 0 (P0) sample was not mixed with borax glycerin, treatment 1 (P1) sample was mixed with 10 ml of borax glycerin, treatment 2 (P2) samples were mixed with 20 ml of borax glycerin, treatment 3 (P3) samples were mixed with 30 ml of borax glycerin, treatment 4 (P4) samples were mixed with 40 ml of borax glycerin, and treatment 5 (P5) samples were mixed with 50 ml of borax glycerin. The results showed that the time of color change and texture of the sample to resemble beef and the preference of Calliphoridae flies for the sample were significantly different (P<0.05). The average value of the time of color change and texture of pork to resemble beef in P0 was 00.00±00.00 (no color change), in P1 was 52.25±1.70, in P2 was 48.5±1.91, in P3 was 44.0±4.54, in P4 was 38.25±2.36, and in P5 was 32.5±4.50. In the preference of fly arrival within 12 hours, the average value obtained in P0 was 189.5 ± 73.09, in P1 was 203.14 ± 38, in P2 was 55.75 ± 64.37, in P3 was 141.3 ± 47.48, in P4 was 213.55 ± 66.9, and in P5 was 32.5 ± 65.0. Samples mixed with borax glycerin did not show any life cycle of Calliphoridae flies. The species obtained in this study belong to the genus Lucilia, namely Lucilia cuprina and Lucilia caesar , and the genus Chrysomya, namely Chrysomya megacephala .